Development of Arabicara: An Arabic Language Learning Application for the Visually Impaired - Alhan Husein; Alif Firmansyah Putra; Azalia Fathimah Dinah; Danny Suggi Saputra; Dimas Arya Nurhakim; Odang Odang (Khazanah Multidisiplin, 2025)
Visually impaired individuals often face limitations in accessing Arabic language learning because conventional media, such as Braille books, do not fully support independent learning. This study aims to develop Arabicara, a cloud-based mobile application featuring text-to-speech, voice navigation, OCR, a dictionary, and interactive exercises. The method used is Research and Development (R&D) with an Agile–Scrum approach, including direct trials with 21 visually impaired respondents. The test results show a significant increase in the average posttest score (80.2) compared to the pretest (47.5). Most respondents stated that the application was easy to access, interactive, and helpful for self-learning, despite issues with the need for a stable internet connection. Thus, Arabicara is considered capable of enhancing the inclusivity of Arabic language learning for the visually impaired.